The Impact Of Adding Notifications For Drug Restriction Information And Digitalization Of Chemotherapy Protocols In Sistema On The Success Of Claiming Oral Antineoplastic Drugs For JKN Outpatients At The Academic Hospital Of Universitas Gadjah Mada - Nofiyanti, Nofiyanti; Septiyorini, Hanifah Icsan; Rakhmayanti, Luthfi; Mahmudah, Puri Nur (Academic Hospital Journal, 2025)
Chemotherapy services in the Rumah Sakit Akademik UGM have collaborated with BPJS Kesehatan so that service costs and drug costs can be covered. The success of submitting claims for service and drug costs to the BPJS Kesehatan depends on the compliance of health workers in selecting a treatment regimen based on national formulary guidelines and clinical service guidelines, and taking action for the benefit of establishing a diagnosis and laboratory examination. Electronic prescribing innovations, the addition of drug restriction information notifications based on the Formularium Nasional, and the digitalization of chemotherapy protocols are expected to help reduce problems related to delays in billing costs to BPJS Kesehatan.Method: The method used in this research is an observational method with a cross-sectional research design. The data collected will then be analyzed by comparing before and after the addition of national formulary drug restrictions to electronic prescriptions and protocol digitization with the help of Sistema and claim reports.Result: Research on the impact of adding drug restriction notification information and digitizing chemotherapy protocols in the Sistema system on the success of claims for oral antineoplastic drugs for outpatient JKN patients at Rumah Sakit Akademik Universitas Gadjah Mada found that 95.7% of the submitted cases were successfully verified by BPJS, while 4.3% of oral antineoplastic cases were pending from January to August 2024.Conclusion: The addition of notification for drug restriction information has proven effective in reducing pending oral antineoplastic claims caused by non-compliance with drug restrictions.